PENGEMBANGAN MEDIA PEMBELAJARAN PAPAN PERKALIAN PINTAR BERBASIS METODE MONTESSORI UNTUK KELAS III SEKOLAH DASAR - Marisa Rahma Tusya’diah (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
This study aims to determine the validity, practicality, and effectiveness of the developed Montessori method-based smart multiplication board learning media. The method applied is the ADDIE research method (Analyze, Design, Development, Implementation, and Evaluation). The targets in this study were third grade students of SD Negeri 53 Prabumulih. Data collection techniques in this study were in the form of validation questionnaires, student response questionnaires and learning outcomes tests in the form of practice questions. The validity results of the three media expert validators and material experts in assessing the quality of the learning media for smart multiplication boards based on the montessori method as a whole obtained a score of 87% with a very valid category. The one to one trial obtained an average of 91.33%, the small group trial obtained an average of 90.83% and the large group trial obtained an average of 91.37% which overall obtained a score of 91.17% in the very practical category. The results of the student question practice test obtained an average of 82.9% with a very effective category. Based on the results of the data obtained, it can be concluded that the smart multiplication board media based on the Montessori method has met the criteria of valid, practical, and effective. Keywords: Multiplication Board, Learning Media, Montessori Method